2022
DOI: 10.3390/e24070956
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Learning under Tilted Empirical Risk Minimization

Abstract: Gradient Learning (GL), aiming to estimate the gradient of target function, has attracted much attention in variable selection problems due to its mild structure requirements and wide applicability. Despite rapid progress, the majority of the existing GL works are based on the empirical risk minimization (ERM) principle, which may face the degraded performance under complex data environment, e.g., non-Gaussian noise. To alleviate this sensitiveness, we propose a new GL model with the help of the tilted ERM cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…( 4), which behaves similarly to q-FFL. While the two objectives show comparable improvements in the evaluations of Li et al [11], their interactions with personalisation are unknown.…”
Section: Fair Federated Learningmentioning
confidence: 97%
See 3 more Smart Citations
“…( 4), which behaves similarly to q-FFL. While the two objectives show comparable improvements in the evaluations of Li et al [11], their interactions with personalisation are unknown.…”
Section: Fair Federated Learningmentioning
confidence: 97%
“…A 𝑞 = 0 corresponds to FedAvg, while larger values prioritise higher losses to improve accuracy on clients for which the federated model underperforms. Li et al [11] develop Tilted Empirical Risk Minimization (TERM), shown in Eq. ( 4), which behaves similarly to q-FFL.…”
Section: Fair Federated Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…where w i ą 0 denote the respective weight coefficients; see, also, Li et al (2021a) and Li et al (2021b) for alternative loss functionals inspired by fair resource allocation (Moulin 2003). One of the most popular FL algorithms, FedAvg FL is strikingly similar to a voting system, which is one of the most studied scenarios in social choice theory.…”
Section: Federated Learningmentioning
confidence: 99%